Source code [videorecording (DVD)] - Jones, Duncan, 1971-; Gyllenhaal, Jake, 1980-; Wright, Jeffrey. (Jeffrey Charles), 1965-; Monaghan, Michelle; Farmiga, Vera; Peters, Russell (Summit Entertainment, 2011)
When Captain Colter Stevens wakes up in the body of an unknown man, he discovers he's part of an experimental government program called the 'Source Code' that enables him to cross over into another man's identity in the last eight minutes of his life. Armed with the task of identifying the bomber of a Chicago commuter train, Colter must relive the incident over and over again, gathering clues until he can solve the mystery and prevent an even deadlier second terrorist attack.